ANALISIS KINERJA PETANI DALAM USAHATANI PADI SAWAH DI KELURAHAN BARUGA KECAMATAN BARUGA KOTA KENDARI - Salahuddin, Salahuddin; Malik, Nurhayu (Jurnal Ilmiah Inovasi dan Komunikasi Pembangunan Pertanian, 2026)
This study aimed to examine the performance of farmers in managing lowland rice farming in Baruga Urban Village, Baruga District, Kendari City. The research was conducted from May to July 2025 in the same location. The study site was selected purposively, based on the fact that the area is a major center for lowland rice production in Kendari City. The study population consisted of all lowland rice farmers in the area, totaling 280 individuals. The sample size was set at 10% of the population, resulting in a sample of 28 lowland rice farmers, selected using simple random sampling. The data analysis employed in this study utilized descriptive statistics with class intervals to characterize the performance of farmers engaged in wetland rice cultivation. The results indicate that the farmers' performance in the study area falls into the "moderate" category. Specifically, the performance of wetland rice farmers in Baruga Urban Village, Baruga District, Kendari City, is classified as moderate. While these farmers have demonstrated good performance regarding the quantity and quality of their produce, as well as precision in managing and developing their farming operations, there is room for improvement to elevate their performance to an "excellent" level.